1996
DOI: 10.1021/ma951747q
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Plasma Polymerization of Perfluorocyclohexane

Abstract: Pulsed versus continuous wave plasma polymerization of perfluorocyclohexane is compared as a function of duty cycle off-time, on-time, and peak power. The chemical composition of the deposited films has been determined by X-ray photoelectron spectroscopy (XPS). A greater retention of the chemical structure associated with the precursor molecule is found for the pulsed plasma polymerization experiments. This can be rationalized in terms of the relative perturbation of reactive species contained in the electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 29 publications
5
42
0
Order By: Relevance
“…Briefly, the same recombination products were detected, with similar trends as well. Moreover, the semi-quantitative analysis revealed that, for each product, the partial pressure at one input power of the continuous discharge is almost the same as that obtained in modulated plasmas at the corresponding average input power, which can be calculated as the DC times the peak power [50,51]. This last result can be explained by the fact that FT-IRAS is not a time-resolved technique.…”
Section: Gas-phase Diagnosticsmentioning
confidence: 85%
“…Briefly, the same recombination products were detected, with similar trends as well. Moreover, the semi-quantitative analysis revealed that, for each product, the partial pressure at one input power of the continuous discharge is almost the same as that obtained in modulated plasmas at the corresponding average input power, which can be calculated as the DC times the peak power [50,51]. This last result can be explained by the fact that FT-IRAS is not a time-resolved technique.…”
Section: Gas-phase Diagnosticsmentioning
confidence: 85%
“…Surface modification of polymers by vacuum nonequilibrium plasmas is well documented in the scientific literature. Examples of vacuum‐plasma chemical‐surface modification8, 13, 14 and physical‐surface modification15–17 plasma‐assisted chemical‐vapor deposition18–21 and surface‐property enhancement (e.g., adhesion improvement22–25) are prevalent. However, examples of polymer‐surface modification at atmospheric pressure with nonequilibrium plasmas are much rarer.…”
Section: Introductionmentioning
confidence: 99%
“…Activated fluorine species are created by the decomposition of OFCB through collision-induced reactions including electron impact dissociation, ion bombardment, and collision with argon metastable species, in addition to radiation-induced reactions including unimolecular excitation and dissociation [13,33,34]. As discussed above, the high reactivity of benzene molecules seriously affects the initiation of the fluorine species when introduced in the DS region, leading to a significant decrease in the quantity of activated fluorine species available for copolymerization.…”
Section: Resultsmentioning
confidence: 99%